PROJECT WORK AS ONE OF THE MEANS CREATIVE LANGUAGE TEACHING - Kholmatova Shakhnoza Muminovna (Web of Journals Publishing, 2024)
The article reveals the essence and practical significance of design work. The goals, objectives, and advantages of the method are given. Project work is a method of developing a problem in detail, which can result in a real positive result, a final product. It is concluded that this method activates the independence, creative and mental activity of students based on practical research of this method.
Keywords: design work, stages of work, tool, application, essence, types, integration, technologies.